The church, food culture, and ecotheology: An ongoing church effort in reducing bushmeat eating in Minahasa, Indonesia - Alva Supit; Agusteivie Telew; Nancy Bawiling (Health for All Nations, 2021)
Minahasa is a Christian-majority region in the Muslim-majority country of Indonesia. Most of the Minahasan people are meat consumers, with an increased consumption rate during festive seasons. Unfortunately, during these seasons, the consumption of non-cattle animals such as wild animals also increases. This eating style was reported to be related to the high prevalence of metabolic diseases in this area. In this paper, we report the effort of the largest church organization in Minahasa to promote healthy eating habits among its congregation, which comprises the majority of the society of the region. More recently, the church has also been incorporating the values of wild animal conservation in its programs in collaboration with a local non-government organization. This ongoing unique phenomenon might serve as a unique example of how a church organization can be involved in public and planetary health as a part of its mission to preach the gospel to every creature.